2013
DOI: 10.1371/journal.pone.0083398
|View full text |Cite
|
Sign up to set email alerts
|

Targeted Expression of Suicide Gene by Tissue-Specific Promoter and MicroRNA Regulation for Cancer Gene Therapy

Abstract: In order to realise the full potential of cancer suicide gene therapy that allows the precise expression of suicide gene in cancer cells, we used a tissue specific Epithelial cell adhesion molecule (EpCAM) promoter (EGP-2) that directs transgene Herpes simplex virus–thymidine kinase (HSV-TK) expression preferentially in EpCAM over expressing cancer cells. EpCAM levels are considerably higher in retinoblastoma (RB), a childhood eye cancer with limited expression in normal cells. Use of miRNA regulation, adjacen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 49 publications
0
11
0
1
Order By: Relevance
“…For such diseases, RNAe holds a promise due to a likely tissue-specificity since it could enhance the target protein expression in a manner dependent on native mRNA distribution. RNAe also showed great simplicity compared with other tissue-specific methods ( 24 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…For such diseases, RNAe holds a promise due to a likely tissue-specificity since it could enhance the target protein expression in a manner dependent on native mRNA distribution. RNAe also showed great simplicity compared with other tissue-specific methods ( 24 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…Danda et al . demonstrated that plasmid carrying the suicide gene was selectively expressed in the cancer cells (retinoblastoma) overexpressing Epithelial cell adhesion molecule (EpCAM) [ 51 ], and Dancer et al . demonstrated in vivo reduction of tumor volume and the number of blood vessels in the study targeting a suicide gene in the endothelium of transgenic mice [ 52 ].…”
Section: Discussionmentioning
confidence: 99%
“…En el retinoblastoma, la terapia génica ha producido reducción y detención del crecimiento de la masa por medio de los mecanismos antiapoptóticos del gen RB1, que no permite su crecimiento. Sin embargo, los efectos inflamatorios severos por el tipo de vector usado han hecho que los estudios se mantengan en fases experimentales (43,44).…”
Section: Terapia Génica En Enfermedades Ocularesunclassified